Muslima theology: the voices of Muslim women theologians - Aslan, Ednan; Hermansen, Marcia K.; Medeni, Elif (Wiener Islamstudien, 2013)
This pioneering volume defines the contours of the emerging engagements of Muslim women scholars from around the world with the authoritative interpretive traditions of Islam, classical and contemporary. Muslima theology, encompassing a range of perspectives and arising from multiple social locations, now claims a place alongside womanist and mujerista readings that interrogate scripture and other forms of religious discourse to empower women of faith to speak for themselves in the interests of gender justice